Strategi Promosi Paperlines Visual Melalui Istagram (@Paperlines_) Untuk Menigkatkan Konsumen - Latifah Dwi Puspitasari; Anita Reta kusumawijaya (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This study aims to determine effective promotion strategies in increasing consumer confidence through Instagram. Communication strategies can be used to measure the success and failure of a communication process. Paperlines Visual is a wedding documentation vendor in Blitar that utilizes Instagram social media to get consumers. Research using descriptive qualitative method. Data collection is done through observation, interviews, and documentation. The subjects of this study were Marketing Manager Paperlines Visual informants and Content Creator Paperlines Visual. The object of this research is the Paperlines Visual promotion strategy using Instagram social media. The theory used is new media theory or theory. The results of this study reveal that by carrying out promotional strategies using Instagram, such as optimizing the bio feature on Instagram accounts, using reviews or testimonials from clients, arranging posting schedules, posting interactive content in uploads on the home page and instagram stories, instagram reels to receive feedback or feedback from their followers. From the upload of Paperlines Visual, it can be seen that the majority of feedback is positive, as can be seen from the comments and direct messages.